Circular economy scientific knowledge in the European Union and China: A bibliometric, network and survey analysis (2006–2016). (1st October 2018) - Türkeli, Serdar; Kemp, René; Huang, Beijia; Bleischwitz, Raimund; McDowall, Will
Abstract: In this article, we analyse the evolution of circular economy (CE) scientific knowledge in the most productive political geographies in the field, namely the European Union (EU) 28 and China by using bibliometric, network and survey analysis. Our objective is to provide a systemic, quantitative, visio-temporal review of the evolution of the CE scientific research field. Using Web of Science (WoS) database and Scopus, we trace the bibliometric characteristics of key research terms, their co-occurrences, publication (co)authorships at multi-level (author, institute, city, region, country), issue journals, literature citations and funding sources. Our findings from co-authorship, citation, co-citation, bibliometric coupling, co-occurrence and network analyses indicate that China and the EU have the highest amount of CE literature published and are each other's primary source of co-authorship. Emerging or reiterated main themes in the joint CE literature between EU and China are emergy analysis, indicators; resource efficiency, food waste, zero waste; eco-cities, lifestyle and governance. There appears a good potential for international cooperation in the sectoral fields of automotive, construction and demolition, critical raw materials; in business, (new) business models, product and services platforms, and from security perspective, resource security, security of supply, given the paucity of co-authorship between China and the EU under these themes. In China; Beijing, Shenyang, Dalian, Shanghai are the most active cities with a central role of Chinese Academy of Sciences at institution level of analysis. The most active EU institute is the Delft University of Technology in South Holland, the Netherlands. In Europe, we observe countries citing CE literature yet with no or few publications. Journal of Cleaner Production is the most important outlet for publications on CE and also for joint publications of CE researchers in both China and EU-28. We conclude our article with future research agendas, and a positive note on existing interests in international cooperation based on our survey participated by highly-cited CE authors. Highlights: China has produced the highest number of CE publications; China and the EU are each other's primary source of co-authorship. Joint themes: emergy, indicators, green finance; resource efficiency, food and zero waste; eco-cities, lifestyle, governance. Product life-cycle extensions, new business models, political economy are seen as the most important research fields for CE. More research is needed on consumer acceptance, rebound effects, social innovation, societal aspects, alternative economies. Policy co-programming, multi-level, multi-domain co-funding, international co-authorship are highly relevant for a CE agenda.